Oligopoly and trade - Neary, P; Leahy, D (University of Oxford, 2010)
In this chapter we present a selective analytic survey of some of the main results of trade under oligopoly. We concentrate on three topics: oligopoly as an independent determinant of trade, as illustrated by the reciprocal-markets model of Brander (1981); oligopoly as an independent rationale for government intervention, as illustrated by strategic trade and industrial policy in the third-market model of Spencer and Brander (1983); and the challenges and potential of embedding trade under oligopoly in general equilibrium as illustrated by the GOLE model of Neary (2002).